2009
DOI: 10.1007/s00432-009-0633-1
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic role of phospho-Src family kinase analysis in tongue cancer

Abstract: Inverse correlation between phospho-Src family kinase and patient survival demonstrates the prognostic role of phospho-Src family kinase in tongue cancer. These findings suggest a novel link between phospho-Src family kinase and TUNEL and c-erbB-2 pathways, tilting the balance toward cell proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…In this context, taking into consideration that FAK and Src have been implicated in the regulation of tumor aggressiveness, it could be speculated that less aggressive tumors need more the ample expression of these enzymes in order to overcome the barriers for their survival, invasion, and metastasis. Moreover, an important observation of the present study was the significant association of Src expression with overall and disease-free patient survival in accordance with previous reports (Ben-Izhak et al 2010;Cheng et al 2011). This observation supports the potential role of Src signaling pathway in the disease progression, including aspects that may affect patients' survival.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this context, taking into consideration that FAK and Src have been implicated in the regulation of tumor aggressiveness, it could be speculated that less aggressive tumors need more the ample expression of these enzymes in order to overcome the barriers for their survival, invasion, and metastasis. Moreover, an important observation of the present study was the significant association of Src expression with overall and disease-free patient survival in accordance with previous reports (Ben-Izhak et al 2010;Cheng et al 2011). This observation supports the potential role of Src signaling pathway in the disease progression, including aspects that may affect patients' survival.…”
Section: Discussionsupporting
confidence: 91%
“…Importantly, a recent immunohistochemical study by Ben-Izhak et al (2010) conducted on 39 mobile tongue SCC cases showed for the first time that Src expression was significantly correlated with lymph node metastasis and patients' survival and borderline with tumor size and stage. Moreover, Src was significantly associated with the progression, recurrence, and prognosis of oral SCCs in Taiwan (Cheng et al 2011).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A number of animal and cell experiments have confirmed that Src and p-Src can be detected in osteosarcoma cells [2022], and in other malignant tumors such as squamous cell carcinoma of the tongue, breast cancer, rhabdomyosarcoma, and Ewing’s sarcoma, Src and p-Src also showed high expression [17,18,2628]. In this study, we used immunohistochemistry to show that the expression percentage of Src and p-Src was 20% and 10% of the 20 osteochondroma cases, respectively, while in 116 cases of osteosarcoma, the expression rate of both proteins was significantly increased, with 62.9% and 64.7% of cases showing high expression of Src and p-Src, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…10,11) SFKs, including Fyn, are non-receptor tyrosine kinases that drive malignancy in various cancers. 12,13) Fyn has also been suggested to be an effector of epidermal growth factor receptor (EGFR) signaling, 14,15) and it is recognized as a potential therapeutic target. 11,16,17) However, little is known about the clinical importance of phosphorylated Fyn (pFyn) in lung adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%